2014
DOI: 10.1007/s10643-014-0680-3
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Disparities in Parent Education: Examining the Effects of Learn the Signs/Act Early Parent Education Materials on Parent Outcomes

Abstract: Early intervention is critical for improved prognosis and quality of life for young children with developmental delays and disabilities. Yet, disparities persist among underserved families with young children. These disparities include knowledge of child development, use of medical providers as referral sources, and later diagnosis. The current study employed a mixed method, randomized controlled trial to examine participant outcomes among low-income, underserved families who received child development informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…LTSAE materials are designed based on behaviour change theory and social marketing techniques (Raspa et al, 2015). Several evaluation studies of LTSAE materials have demonstrated an impact on public awareness and parent attitudes and practice (Burt, 2013;Graybill, Self-Brown, Lai, Vinoski, McGill, & Crimmins, 2016;Patel, 2007;Westat, 2015;Crimmins, Graybill, & Vinoski, 2013). Specifically, these studies have established that population-level awareness of ASD increased during the first two years of the LTSAE campaign and that parents had positive perceptions of LTSAE materials (Graybill et al, 2016;Raspa, et al, 2015;Patel, 2007;Westat, 2015).…”
Section: 'Learn the Signs Act Early'mentioning
confidence: 99%
See 1 more Smart Citation
“…LTSAE materials are designed based on behaviour change theory and social marketing techniques (Raspa et al, 2015). Several evaluation studies of LTSAE materials have demonstrated an impact on public awareness and parent attitudes and practice (Burt, 2013;Graybill, Self-Brown, Lai, Vinoski, McGill, & Crimmins, 2016;Patel, 2007;Westat, 2015;Crimmins, Graybill, & Vinoski, 2013). Specifically, these studies have established that population-level awareness of ASD increased during the first two years of the LTSAE campaign and that parents had positive perceptions of LTSAE materials (Graybill et al, 2016;Raspa, et al, 2015;Patel, 2007;Westat, 2015).…”
Section: 'Learn the Signs Act Early'mentioning
confidence: 99%
“…There is also evidence (based on parent self-report) that LTSAE materials impacted some parent outcomes, including increased tracking of developmental milestones in their own child(ren), increased comfort with and likelihood of following up with a professional as a result of developmental concern, and decreased concern about their own child's development (Campbell, Greenberg, Gallagher, Stoneburg & Simmons, 2018;Graybill et al, 2016;Westat, 2015).…”
Section: 'Learn the Signs Act Early'mentioning
confidence: 99%
“…En el caso específico de la Educación Parvularia, el material didáctico constituye un elemento central ya que, en el proceso de formación de niños, la comunicación mediante material educativo juega un papel fundamental para la interacción y el aprendizaje efectivo (Slot et al, 2015). Por lo tanto, en la preparación de los futuros formadores, la infraestructura, el equipamiento y el material educativo son de la mayor importancia para generar procesos educativos eficaces y eficientes (Graybill et al, 2016).…”
Section: Recursos Educativosunclassified
“…Act Early . Milestone Moments booklets; Graybill et al., ). Screening , however, is a more formal early detection technique wherein HCPs use well‐validated normed instruments to query parents about their child's development and social‐emotional functioning.…”
Section: Introductionmentioning
confidence: 99%